Global research on RNA vaccines for COVID-19 from 2019 to 2023: a bibliometric analysis - Chen, Ziyi; Liu, Zhiliang; Feng, Yali; Shi, Aochen; Wu, Liqing; Sang, Yi; Li, Chenxi (Frontiers in Immunology, 2024)
Background Since the global pandemic of COVID-19 has broken out, thousands of pieces of literature on COVID-19 RNA vaccines have been published in various journals. The overall measurement and analysis of RNA vaccines for COVID-19, with the help of sophisticated mathematical tools, could provide deep insights into global research performance and the collaborative architectural structure within the scientific community of COVID-19 mRNA vaccines. In this bibliometric analysis, we aim to determine the extent of the scientific output related to COVID-19 RNA vaccines between 2019 and 2023. Methods We applied the Bibliometrix R package for comprehensive science mapping analysis of extensive bibliographic metadata retrieved from the Web of Science Core Collection database. On January 11th, 2024, the Web of Science database was searched for COVID-19 RNA vaccine-related publications using predetermined search keywords with specific restrictions. Bradford’s law was applied to evaluate the core journals in this field. The data was analyzed with various bibliometric indicators using the Bibliometrix R package. Results The final analysis included 2962 publications published between 2020 and 2023 while there is no related publication in 2019. The most productive year was 2022. The most relevant leading authors in terms of publications were Ugur Sahin and Pei-Yong, Shi, who had the highest total citations in this field. The core journals were Vaccines, Frontiers in Immunology, and Viruses-Basel. The most frequently used author’s keywords were COVID-19, SARS-CoV-2, and vaccine. Recent COVID-19 RNA vaccine-related topics included mental health, COVID-19 vaccines in humans, people, and the pandemic. Harvard University was the top-ranked institution. The leading country in terms of publications, citations, corresponding author country, and international collaboration was the United States. The United States had the most robust collaboration with China. Conclusion The research hotspots include COVID-19 vaccines and the pandemic in people. We identified international collaboration and research expenditure strongly associated with COVID-19 vaccine research productivity. Researchers’ collaboration among developed countries should be extended to low-income countries to expand COVID-19 vaccine-related research and understanding.